2018
DOI: 10.9734/ajpr/2018/v1i124582
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Birth Weight and Gender of Newborn Infants

Abstract: Introduction: Birth weight is an important determinant of infant morbidity and mortality. Its effect extends upto adult life and may explain some non-communicable diseases that may occur in adult life. In general, males weigh more than females. Birth weight is categorised into three levels, viz., low, normal and high. This study analysed the relationship between gender and the categories of birth weights. Materials and Methods: Data on babies’ gender and birth weights from 961… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The data reported no significant difference in birth weight between the genders in low birth weight category. [ 11 ] Similarly, Oladeinde et al . ( n = 780) in their study on determinants of low birth weight found that the prevalence of LBW was higher in female newborns but not statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…The data reported no significant difference in birth weight between the genders in low birth weight category. [ 11 ] Similarly, Oladeinde et al . ( n = 780) in their study on determinants of low birth weight found that the prevalence of LBW was higher in female newborns but not statistically significant.…”
Section: Discussionmentioning
confidence: 96%